Cardiac structure and function recovery in acromegaly after treatment: insights from cardiac magnetic resonance imaging - Chen, Yu; Li, Yangjie; Tang, Yu; Li, Jing; Yu, Yerong; Tan, Huiwen; Cai, Bowen; Jiang, Shu; Wang, Wei; Zheng, Songping; Zhou, Peizhi; Wei, Yi; et al. (Frontiers in Endocrinology, 2025)
PurposeCardiac magnetic resonance imaging (CMRI) provides a detailed method for understanding the specific cardiovascular alterations associated with acromegaly. This study aimed to evaluate the impact of personalized treatment on cardiac structure, function, and myocardial tissue characteristics using CMRI, and to assess the effects of biochemical remission on improving cardiovascular complications in acromegaly patients.MethodThirty-nine acromegaly patients were enrolled from July 2020 to February 2023 at West China Hospital of Sichuan University. Comprehensive cardiac assessments were conducted using a 3.0 T MRI scanner at baseline and one year after individualized treatment.ResultsAmong the 30 patients who completed both baseline and one-year follow-up CMRI examinations, significant reductions in left ventricular (LV) wall thickness and end-diastolic diameter were observed compared to baseline (both P < 0.05). Left ventricular mass (LVM) and mass index (LVMi) also significantly decreased (LVM: 90.17 ± 25.86 g vs. 101.18 ± 26.10 g, P=0.007; LVMi: 50.01 ± 12.56 g/m2vs. 56.20 ± 13.01 g/m², P=0.008). Additionally, T2 values showed a significant reduction following individualized treatment (basal T2: 39.12 ± 2.82 ms vs. 42.91 ± 4.38 ms, P<0.001; apical T2: 41.96 ± 3.87 ms vs. 45.13 ± 4.87 ms, P=0.021). Compared to healthy controls, patients who achieved biochemical remission exhibited increased LV inferior septal thickness and elevated extracellular volume (ECV) values. However, T2 value in the basal layer of the LV was significantly lower in the remission group compared to healthy controls.ConclusionPatients with acromegaly exhibited LV hypertrophy, enlargement, myocardial fibrosis and impaired systolic function assessed by CMRI compared with healthy controls. Individualized treatment led to partial reversed of these abnormalities, particularly in those who achieved biochemical remission.